Antiinflammatory Activity of Commiphora caudata [Wight and Arn] - SIVAKUMAR, T.; KANNAN, K.; KANNAPPAN, N.; KATHIRESAN, K. (Asian Journal of Chemistry, 2010)
Ethyl acetate and methanolic extracts of Commiphara caudata syn: Protium caudatum were tested for antiinflammatory activity in rats by carrageenan induced hind paw oedema method. Both ethyl acetate extract and methanolic extract of Commiphara caudata (200 mg/kg of body weight) exhibited significant antiinflammatory activities when compared with control. Indomethacin was used as a reference antiinflammatory drug.